SISTEM INFORMASI PELAYANAN SURAT KETERANGAN USAHA DAN DOMISILI DESA CIKALONG - Ningsih , Neng Cahya; Sopiandi, Ii; Abdurahman, Dede (Universitas Majalengka, 2025)
Administrative services at the village level are essential in meeting community needs, particularly in issuing official documents such as the Business Certificate (Surat Keterangan Usaha/SKU) and the Domicile Certificate (Surat Keterangan Domisili/SKD). In Cikalong Village, Sukahaji Sub-district, Majalengka Regency, these processes are still performed manually, leading to delays, recording errors, and archiving difficulties that decrease service efficiency and quality. This study aims to design and develop a web-based Information System for SKU and SKD services to overcome these problems. The system was developed using the waterfall model, including requirement analysis, design, implementation, and testing. The results indicate that the system improves processing speed, reduces administrative errors, and facilitates data storage and retrieval. Furthermore, it enhances transparency and accountability in public services. Implementation of this system is expected to deliver faster, more effective, and efficient administrative services while supporting modern village governance aligned with community needs.